Vulnerability and gender:: an approach to disaster risks from southern Mexico - Soares, Denise (Sustainability in Debate, 2017)
This paper presents, on the one hand, a reflection about the triad vulnerability-gender and disasters risk, and on the other, a case study in San Felipe, Yucatan, Mexico, about the perceptions of women and men regarding the ability of institutions and population in reacting to hurricane disasters from a gender perspective. To learn about the local social perceptions, surveys and interviews with key informants have been used. The results demonstrate severe problems in the authority of the municipality responsible for the promotion of the disaster risk management and gender equality. Therefore, there is an important need to strengthen both social and institutional capacities in the area of risk management with gender equality.